The Influence of Corporate Social Responsibility (CSR) on Customer Loyalty Mediated by Customer Satisfaction, Trust, Word of Mouth (WOM), and Company Reputation - Wulan Rahmawati; Unggul Kustiawan (Dinasti Publisher, 2024)
Retaining customers is important for companies because the cost of acquiring new customers is much greater than the cost of maintaining relationships with current customers. This is because loyal customers will certainly provide a positive image for the company and generate word of mouth promotion in acquiring new customers. The purpose of this study is to examine the effect of Corporate Social Responsibility (CSR) on customer loyalty mediated by Customer Satisfaction, Trust, Word of Mouth (WOM), and Corporate Reputation. Type data Which used is data primary, is data Which sourced or managed in a way direct by researcher. Collection data in study This done through questionnaire with using google-form . The population of this study were customers who had been Government Banks for more than 1 (one) year, namely Bank Mandiri, Bank BNI, and Bank BRI and were over 17 years old (seventeen years old). The sample in this study was 100 customers of Government Banks, namely Bank Mandiri, Bank BNI, and Bank BRI who have used and are still using the services of these banks. This study uses the Structural Equation Model (SEM) approach with a measurement model assisted by the Smart PLS program version 3.2.9. Furthermore results study show that corporate social responsibility has a significant positive effect on customer satisfaction, trust, word of mouth, corporate reputation , and customer loyalty. Then the variables customer satisfaction, trust, corporate reputation found has a significant positive effect on customer loyalty, but the word of mouth variable does not affect customer loyalty . Furthermore, it was found that customer satisfaction, trust, and corporate reputation can mediate the relationship between corporate social responsibility and customer loyalty . However, the corporate social responsibility variable does not affect customer loyalty with word of mouth as a mediator.